Allergen Composition, Marketing Claims, and Affordability of Pediatric Sunscreens. Issue 6 (11th November 2022) - Rick, Jonathan W.; Brannon, Madalyn; De, Devea R.; Shih, Terri; Hsiao, Jennifer L.; Shi, Vivian Y.
Abstract : Background: Childhood sun exposure is associated with development of future skin cancers. Sunscreens are an important tool to prevent harmful ultraviolet rays. Objectives: The aims of the study are to evaluate sunscreens targeted to children and to analyze cost, marketing claims, ingredients, and allergens to help consumers select products. Methods: The top 50 pediatric sunscreens across retailers were analyzed for their cost, marketing claims, ingredients, vehicles, and containers. Ingredients were compared with the American Contact Dermatology Society 2020 Core Allergen List. Results: The mean price was 6.20 per ounce (range, 0.25–39.98). The mean sun protection factor was 48.5 (range, 30–100; SD, 48.5). There was a mean of 17.5 ingredients and a mean of 1.1 allergens in products. On average, products marketed as "sensitive skin" were not only significantly more expensive (8.90 vs 3.50 per ounce, P = 0.01) but also were significantly more likely to not contain any allergens (36.0%, n = 18 vs 12%, n = 6; P = 0.05). Products with mineral-only UV blockers were significantly less likely to have any allergen when compared with products that had chemical UV blockers (5.6%, n = 1 vs 94.4%, n = 17; P = 0.02). Conclusions: The current market of pediatric sunscreens varies significantly in price, marketing claims, and active ingredients. Products marked as suitable for sensitive skin had significantly fewer allergens, but a majority of these products still had at least one allergen. Many sunscreens contain contact allergens, which is an important selection consideration.